Gamificación como estrategia para la expresión del lenguaje de los niños y niñas del sub nivel inicial 2 de la Unidad Educativa Cristóbal Colón, del cantón Babahoyo - Salazar Chichande, Iliana Denisse (2022)
Gamification at the initial level includes a fundamental role in the acquisition of knowledge, skills, abilities and techniques, as well as developing better concentration, memory and proper behavior in boys and girls, working hard in the process of socialization and application of the games as a positive and entertaining tool that will allow children to learn while playing. Language is innate in human beings, but it is at these early ages where more emphasis should be placed on its development since children are in a malleable stage, that is, this is the right time to work on the expression of language. , which must be perfected little by little since it is known that a good development of the language will allow students in the future not to have any type of inconvenience throughout their academic and professional life. Gamification and language go hand in hand since there is no better way for students to learn than with the work game modality, where toddlers will not only play but also learn the guidelines and relevant topics that should be cultivated at their age.